Role of Cell Wall Polyphosphates in Phosphorus Transfer at the Arbuscular Interface in Mycorrhizas - Nguyen, Cuc Thi; Saito, Katsuharu (Frontiers in Plant Science, 2021)
Arbuscular mycorrhizal fungi provide plants with soil mineral nutrients, particularly phosphorus. In this symbiotic association, the arbuscular interface is the main site for nutrient exchange. To understand phosphorus transfer at the interface, we analyzed the subcellular localization of polyphosphate in mature arbuscules of Rhizophagus irregularis colonizing roots of Lotus japonicus wild-type and H+-ATPase ha1-1 mutant, which is defective in phosphorus acquisition through the mycorrhizal pathway. In both, the wild-type and the ha1-1 mutant, polyphosphate accumulated in the cell walls of trunk hyphae and inside fine branch modules close to the trunk hyphae. However, many fine branches lacked polyphosphate. In the mutant, more fine branch modules showed polyphosphate signals compared to the wild-type. Notably, polyphosphate was also observed in the cell walls of some fine branches formed in the ha1-1 mutant, indicating phosphorus release from fungal cells to the apoplastic regions. Intense acid phosphatase activity was detected in the periarbuscular spaces around the fine branches. Furthermore, double staining of acid phosphatase activity and polyphosphate revealed that these had contrasting distribution patterns in arbuscules. These observations suggest that polyphosphate in fungal cell walls and apoplastic phosphatases may play an important role in phosphorus transfer at the symbiotic interface in arbuscules.